Hydrogen atom kinetics in capacitively coupled plasmas. (6th April 2017) - Nunomura, Shota; Katayama, Hirotaka; Yoshida, Isao
Abstract: Hydrogen (H) atom kinetics has been investigated in capacitively coupled very high frequency (VHF) discharges at powers of 16–780 mW cm –2 and H2 gas pressures of 0.1–2 Torr. The H atom density has been measured using vacuum ultra violet absorption spectroscopy (VUVAS) with a micro-discharge hollow cathode lamp as a VUV light source. The measurements have been performed in two different electrode configurations of discharges: conventional parallel-plate diode and triode with an intermediate mesh electrode. We find that in the triode configuration, the H atom density is strongly reduced across the mesh electrode. The H atom density varies from ∼10 12 cm −3 to ∼10 10 cm −3 by crossing the mesh with 0.2 mm in thickness and 36% in aperture ratio. The fluid model simulations for VHF discharge plasmas have been performed to study the H atom generation, diffusion and recombination kinetics. The simulations suggest that H atoms are generated in the bulk plasma, by the electron impact dissociation (e + H2 → e + 2H) and the ion–molecule reaction (H2 + + H2 → H 3 + + H). The diffusion of H atoms is strongly limited by a mesh electrode, and thus the mesh geometry influences the spatial distribution of the H atoms. The loss of H atoms is dominated by the surface recombination.